Application of hiPSC as a Drug Tester Via Mimicking a Personalized Mini Heart - Wei, Li; Xia, Shutao; Li, Yifei; Qi, Yan; Wang, Yue; Zhang, Donghui; Hua, Yimin; Luo, Shuhua (Frontiers in Genetics, 2022)
Human induced pluripotent stem cells (hIPSC) have been used to produce almost all types of human cells currently, which makes them into several potential applications with replicated patient-specific genotype. Furthermore, hIPSC derived cardiomyocytes assembled engineering heart tissue can be established to achieve multiple functional evaluations by tissue engineering technology. This short review summarized the current advanced applications based on the hIPSC derived heart tissue in molecular mechanisms elucidating and high throughput drug screening.